2023
DOI: 10.1038/s41541-023-00661-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of retinal vascular occlusion after COVID-19 vaccination

Abstract: Coronavirus disease 2019 (COVID-19) vaccines are associated with several ocular manifestations. Emerging evidence has been reported; however, the causality between the two is debatable. We aimed to investigate the risk of retinal vascular occlusion after COVID-19 vaccination. This retrospective cohort study used the TriNetX global network and included individuals vaccinated with COVID-19 vaccines between January 2020 and December 2022. We excluded individuals with a history of retinal vascular occlusion or tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Li and colleagues’ conclusion is based on all types of COVID-19 vaccinations, not specifically mRNA vaccinations. However, they did report the risk of RVO, specifically with mRNA vaccinations, and found no association between vaccination and RVO development at 12 weeks, which agreed with our findings …”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Li and colleagues’ conclusion is based on all types of COVID-19 vaccinations, not specifically mRNA vaccinations. However, they did report the risk of RVO, specifically with mRNA vaccinations, and found no association between vaccination and RVO development at 12 weeks, which agreed with our findings …”
mentioning
confidence: 97%
“…In Reply We appreciate the letters regarding our article by Dorney et al in which messenger RNA (mRNA) COVID-19 vaccinations were not associated with retinal vascular occlusions (RVO). To summarize, the concerns with our study are in relation to Li and colleagues’ comparable article, our choice of a 21-day time frame and the association between first and second vaccination, evaluation of confounder variables, and control group selection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the relatively short 21-day time frame used in some studies may not be sufficient to fully assess the potential cause-effect association between COVID-19 vaccinations and retinal vascular occlusion (RVO). In a study published in May 2023 by Li et al, a relatively longer time frame was associated with somewhat different conclusions. In their study, 739 066 COVID-19–vaccinated patients from the same TriNetX database with a 1:1 propensity-matched unvaccinated cohort were assessed for occurrences of RVO using the same codes.…”
mentioning
confidence: 99%
“…Also, several studies have reported RVO after the second dose or booster of the mRNA COVID-19 vaccination, while other reports of vaccine-related occlusion of the central retinal artery/vein have presented no difference between the first and second dose of the COVID-19 vaccination . Dorney et al reported a higher risk of RVO after the first dose of the mRNA COVID-19 vaccination compared with the second dose.…”
mentioning
confidence: 99%